Molecular basis of fruit development - Robert G. Franks (Frontiers Research Topics, 2014)
The fruit is an important plant structure. Not only does it provide a suitable environment for seeds to develop and serve as a vehicle for seed disposal, but it is also an indispensable part of the human diet. Despite its agronomic and nutritional value and centuries of intensive genetic selection, little is known about the molecular mechanism of its development or the evolution of its diverse forms. The last few years have witnessed a surge of investigations on the early stages of fruit development propelled by the advancement of high throughput sequencing technology, genome sequencing of fruit bearing species, and detailed molecular insights based on studies of model organisms. This research topic is focused on early stage fruit development that ranges from pre-fertilization patterning of the female ovary through post-fertilization fruit initiation and growth. Provided by the renowned experts in the field, these papers are intended to highlight recent progress and shed light on different aspects of fruit development from structure, function, to molecular genetics, and evolution.